2018
DOI: 10.1113/ep087189
|View full text |Cite
|
Sign up to set email alerts
|

Serelaxin attenuates renal inflammation and fibrosis in a mouse model of dilated cardiomyopathy

Abstract: New Findings What is the central question of this study?The aim was to determine the renoprotective effects of serelaxin in the setting of chronic heart failure. What are the main findings and its importance?Our data indicate that serelaxin can reduce renal fibrosis and inflammation in experimental heart failure. Currently, there are no effective treatments to rescue renal function in heart failure patients, and our data suggest that serelaxin might have the potential to reduce renal fibrosis and inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…In addition to cardiac phenotypes, we observed renal atrophy in mice subjected to 27G TAC. Renal atrophy was reported in a mouse model of dilated cardiomyopathy, with increased tubulointerstitial and glomerular fibrosis, alongside reduced renal function 34 . Since chronic heart failure can promote chronic kidney failure in both humans and in mouse studies 35 , we decided to investigate this phenotype further and found renal atrophy secondary to 27G TAC, in the absence of renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cardiac phenotypes, we observed renal atrophy in mice subjected to 27G TAC. Renal atrophy was reported in a mouse model of dilated cardiomyopathy, with increased tubulointerstitial and glomerular fibrosis, alongside reduced renal function 34 . Since chronic heart failure can promote chronic kidney failure in both humans and in mouse studies 35 , we decided to investigate this phenotype further and found renal atrophy secondary to 27G TAC, in the absence of renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The half life time of Serelaxin in blood is 6-8 hours in humans and 4-6 hours in rats 12,39 . Authors of previous publications, which investigated the effects Serelaxin on brain injury, either used a micro pump for continuous delivery of Serelaxin over a long period of time or evaluated the effects of the drug in short (4 hours) term studies [40][41][42][43] . In our preliminary experiments we figured out that P7 rat pups tolerate implantation of a mini pump rather badly.…”
Section: Discussionmentioning
confidence: 99%
“…Renoprotective effects of relaxin, including attenuation of fibrosis, have been noted in patients with several diseases, such as dilated cardiomyopathy or age-related renal fibrosis [ 32 , 33 , 34 ]. In our cohort, relaxin expression was lower in tumors than in normal adjacent tissue.…”
Section: Discussionmentioning
confidence: 99%
“…RLN2 is a small, 6 kDa hormone that is involved in physiological and pathological conditions. Its activity during pregnancy and its involvement in several tumors have been widely described [ 27 , 28 , 29 , 30 , 31 , 32 ], although the role of RLN2 in RCC is not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation